2006
DOI: 10.2355/isijinternational.46.169
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Aluminum and Oxygen and Sulfur Partitions for Molten Iron and a CaO-Al2O3-ZrO2 Slag in Equilibrium

Abstract: The relationship between the aluminum-oxygen and sulfur distribution ratio for molten iron and a CaO-Al 2 O 3 -ZrO 2 slag in equilibrium at 1 873 K was studied using an Al 2 O 3 or CaO-stabilized ZrO 2 crucible. The slag and molten iron equilibrated with CaO·2Al 2 O 3 and Css (cubic solid solution in CaO-ZrO 2 system) in the Al 2 O 3 crucible, and with CaO · ZrO 2 and Css in the ZrO 2 crucible. These equilibrium states coincided with the phase diagram of CaO-Al 2 O 3 -ZrO 2 . From the concentrations of aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The determination of the activity of Al 2 O 3 has been reported by many researchers . Figure shows the historic timeline for the typical study of Al 2 O 3 activity measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the activity of Al 2 O 3 has been reported by many researchers . Figure shows the historic timeline for the typical study of Al 2 O 3 activity measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the activity of Al 2 O 3 has been reported by many researchers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Figure 1 shows the historic timeline for the typical study of Al 2 O 3 activity measurement. Lots of researchers from various countries have developed different methods to accurately measure the activity of Al 2 O 3 in the slag.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tanabe et al observed that the sulfur distribution ratio (log L S ) between the molten iron equilibrated with the CaO-Al 2 O 3 -ZrO 2 slags saturated by CaAl 4 O 7 or CaZrO 3 phases linearly increased with increasing aluminum content (log [mass%Al]) in iron melt with the slope of 2/3 at 1873 K. 4) From this result, they concluded that the oxygen potential between metal and slag was controlled by the [Al]-[O] equilibrium reaction. Although the nitride capacity of the CaO-SiO 2 -Al 2 O 3 -ZrO 2 slags was reported by Sasabe et al, 5) the effect of ZrO 2 on the sulfide capacity of the calcium silicate slags that were used for sulfur removal from the austenitic stainless steel melts is not available in the literature.…”
Section: Introductionmentioning
confidence: 99%